(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The location of the buses in the basement of the new bus station in Bratislava, supplemented by two further parking floors below, shifted the foundation joint of the new bus station to a depth of approximately 14 m. The maneuvering space for the buses required unusually large distances between the supporting columns. In extreme cases, it was necessary to transfer a vertical load of more than 30,000 kN from the column to the subsoil. Only a relatively thin layer of Quaternary gravel remained between the footing bottom and the Neogene soils. The whole area was designed to be based on deep foundations. As this was a construction of the 3rd geotechnical category, it was necessary to verify the bearing capacity and quality of the piles. The applied test methods (especially the dynamic load tests) confirmed the correct design and implementation of piles.